An Analysis of Freedom to Learn Curriculum Implementation at Jakarta’s English Primary School Teachers - Hadi, Muhamad Sofian; Izzah, Lidiyatul; Khatun, Aisyah; Gita, Gita (English Language in Focus (ELIF), 2024)
Freedom to Learn Curriculum (Kurikulum Merdeka) is a new curriculum issued by the ministry of education as one of the innovation in improving the quality of education in Indonesia. The rise of freedom to learn curriculum as one of the strategic decision in pandemic Covid-19 era. Challenges in implementing new curriculum come with various complaints from majority of teachers and it happen also for primary school teacher in Jakarta. The most element factors that make the implementation of new curriculum deals with narrow understanding of meaning and function in new curriculum. The research focus on analyzing the implementation of freedom to learn curriculum for primary school teacher in Jakarta. The research uses qualitative approach with case study to know the challenge and difficulties of primary school teacher in Jakarta in implementing freedom to learn curriculum (Kurikulum Merdeka). Finding of the study indicating teachers feel difficult to use various kind of teaching tools and aid in making interactive teaching and learning. Based on teacher’s and student’s perspectives, freedom to learn curriculum need to have a clear and comprehensive guidance in order to make the teacher improve their teaching skills in order to bring new transformation for the students.